UNSEEN TUBERCULOSIS: STUDY AMONG INPATIENTS OF A TERTIARY CARE HOSPITAL OF NORTH KARNATAKA - AKASH R JADHAV,; DRPRASHANT KUMAR,; NAGAPPAN MADHAPPAN,; POONAM P SHINGADE, (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: Tuberculosis (TB) remains a significant global health challenge, particularly in high-burden countries like India. However, high proportion of people never diagnosed or treated. Delayed diagnosis poses a significant threat to hospital inpatients, health-care workers, and medical trainees. Hence, systematic screening of high-risk groups, including hospital inpatients, has been recommended as a strategy to identify TB. Using signs and symptoms as an independent screening tool remains a global challenge for its relatively low accuracy. However, it could still be of value when it was used in a specific target population like inpatients of hospital. Hence, this study is aimed to determine the proportion of presumptive and active TB cases among inpatients. Methods: A hospital-based cross-sectional study was conducted among inpatients above 18 years of age admitted in non-emergency wards admitted during March to April 2023 at ESIC Hospital in Kalaburagi. A pre-existing TB diagnosis and patients admitted to critical care units were excluded. The convenient sampling method was used to recruit participants. Data were collected through using a pre-designed, semi-structured questionnaire. The patients who presented with one of the four symptoms for screening had undergone investigations such as cartridge-based nucleic acid amplification test, chest X-ray, and sputum microscopy to confirm the diagnosis, and the findings were recorded as proportion. Results: Out of 1363 inpatients, 35 (2.5%) patients had classified as presumptive TB case. Out of 35, 3 (8.57%) were found to be actual TB cases. All patients who had positive results for TB were young patients and belonged to low socioeconomic class. Two of three were rifampicin-sensitive TB cases. Conclusion: Timely screening of the patient’s is of utmost importance to avoid further spread of TB infection among inpatients. The higher prevalence of actual TB cases in younger adults needs further exploration.